Assessing reparability: simple tools for estimation of costs and performance loss of earthquake damaged reinforced concrete buildings. (6th January 2015) - Polese, Maria; Di Ludovico, Marco; Marcolini, Marco; Prota, Andrea; Manfredi, Gaetano
Summary Tools for assessing building reparability via the estimation of expected performance loss (PL) and associated costs for repair of existing RC building classes damaged by an earthquake are presented. The assessment approach relies on the availability of a number of suitably developed: (i) capacity curves for representative building classes; (ii) curves relating global ductility demand μ to the expected PL for the same classes; and (iii) PL–cost for repair relationship calibrated on database collecting cost data of more than 2300 buildings damaged after 2009 L'Aquila earthquake. The tools are developed applying a simplified procedure involving the simulated design of existing building classes, the assumption of predefined collapse mechanism types and the analyses of the seismic behavior of equivalent SDOF systems representative of 'intact' and 'damaged' structures after an earthquake. The use of these tools may give useful preliminary indications to decision makers for establishing reparability priorities in the aftermath of damaging earthquakes or to insurance companies to value sound insurance premium for existing building classes. Copyright © 2014 John Wiley & Sons, Ltd.